Well Deliverability Analysis Using Modified Isochronal Test: Study Case on AG Gas Well: Analisis Well Deliverability Menggunakan Modified Isochronal Test: Studi Kasus Pada Sumur Gas AG - Gushari, Akba; Nirmala, Gerry Sasanti; Yulianto, Yudha (Journal of Earth Energy Science, Engineering, and Technology, 2024)
The AG Well is a gas well that undergoes well testing utilizing the Modified Isochronal Test method to assess the reservoir characteristics of the NVR Field. In this paper, Type Curve and Horner Plot are analyzed for Pressure Build Up test and well deliverability determination using C and n method to obtain Absolute Open Flow Potential value of NVR reservoir to construct inflow performance relationship curve and Vertical Lift Performance of the well. The reservoir model of Two Porosity Slab and Boundary Intersecting Fault - 31° with an AOFP of 10574.8 MSCF/d was made with Ecrin software.